Development of PISA-type questions and activities using election context to determine students' mathematical reasoning - Sylvenny Mirandah; Zulkardi; Ratu Ilma Indra Putri (Jurnal Elemen)
The importance of developing PISA-type questions and learning activities is to familiarize students with these questions. This study employs a research design with development studies that include the stages of preliminary evaluation and formative evaluation. This research was conducted in response to the low mathematical reasoning skills of students in Indonesia, focusing on eighth-grade junior high school students. Qualitative findings were obtained from field data in the form of interviews, photos, and videos of the activities. The results of this study produced six units of activity questions and three units of evaluation questions on the theme of elections, which are valid and practical for enhancing mathematical reasoning abilities of eighth-grade students. The average score of students for Activity 1, Activity 2, and evaluation questions reached 53.45, indicating the potential effect of PISA-type questions and activities in the context of uncertainty and data with the theme of elections on students' mathematical reasoning skills, which are categorized as adequate. The reasoning indicator that appeared most frequently was the ability to make a conjecture, while the ability to manipulate mathematics was rarely observed. Overall, PISA-type questions and activities in an election context can be used to strengthen students' mathematical reasoning abilities.